Ischemic stroke after COVID-19 bivalent vaccine administration in patients aged 65 years and older in the United States - Maria P. Gorenflo; Pamela B. Davis; David C. Kaelber; Rong Xu (npj Vaccines, 2023)
Abstract The Centers for Disease Control and Prevention announced in January 2023 a potential connection between administration of the Pfizer novel coronavirus disease-2019 (COVID-19) bivalent vaccine booster and ischemic stroke (IS). A retrospective cohort study was conducted to compare the hazard of IS in patients aged 65 years and over administered the Pfizer bivalent booster versus those administered the Pfizer/Moderna monovalent or Moderna bivalent boosters. De-identified patient electronic health data were collected from TriNetX, a cloud-based analytics platform that includes data from over 90 million unique patients in the United States. Patients aged 65 years and over at the time of administration of a Pfizer bivalent, Moderna bivalent, or Pfizer/Moderna monovalent booster were included for analysis. Cohorts were propensity-score matched. The hazard ratios (HR) and 95% confidence intervals (CI) for IS between matched cohorts at 1–21 and 22–42 days after booster administration were calculated. There was reduced hazard of IS in the Pfizer bivalent cohort compared to the monovalent cohort at both timepoints: 1–21 days after vaccination (HR: 0.54, 95% CI: 0.47–0.62), and 22–42 days after vaccination (HR: 0.62, 95% CI: 0.54–0.72) (n = 79,036 patients per cohort). There was reduced hazard of IS in the Pfizer bivalent cohort compared to the Moderna bivalent cohort at 1–21 days after vaccination (HR: 0.75, 95% CI: 0.58–0.96) (n = 26,962 patients per cohort). This analysis provides no evidence that the Pfizer bivalent vaccine is associated with increased hazard of IS compared to the monovalent or Moderna bivalent vaccines.